The effect of chemical clarification of oral fluids on porcine epidemic diarrhea virus antibody responses. (November 2018) - Poonsuk, Korakrit; Giménez-Lirola, Luis G.; Magtoto, Ronaldo L.; Ji, Ju; Baum, David H.; Rademacher, Christopher J.; Brown, Justin T.; Zhang, Jianqiang; Wang, Chong; Main, Rodger G.; Zimmerman, Jeffrey J.
Routine testing of breeding herd oral fluid (OF) samples for porcine epidemic diarrhea virus (PEDV) IgG and/or IgA is used to track levels of PEDV immunity over time. However, OFs contain particles of feed, feces, and inorganic material that detract from the quality of the sample. We clarified swine OF samples using lyophilized chitosan-based formulas (A–C) tested by PEDV IgG and IgA ELISAs. To evaluate both the immediate and residual effects of treatment on antibody detection, samples were tested immediately post-treatment, then stored at 4°C and retested at 2, 4, and 6 days post-treatment (DPT). Formulations were shown to effectively clarify samples. Statistical analysis comparing treated to untreated OF samples at 0 DPT found that neither chitosan nor Tween 20 affected the OF ELISA IgA and IgG sample-to-positive (S/P) ratio results ( p > 0.05). Furthermore, pairwise comparisons of 0 DPT to 2, 4, and 6 DPT results detected no significant differences ( p > 0.05) in IgA and IgG S/P ratios (i.e., treated OF samples were stable over time). Therefore, chitosan efficiently clarified OF specimens without affecting the results of the PEDV IgG and IgA antibody ELISAs.